2016
DOI: 10.1155/2016/7203980
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Where They Give Birth? Determinants of Place of Delivery among Women in Rural Ghana

Abstract: Background. There is a paucity of empirical literature in Ghana on rural areas and their utilisation of health facilities. The study examined the effects of the sociodemographics of rural women on place of delivery in the country. Methods. The paper made use of data from the 2014 Ghana Demographic and Health Survey. Women from rural areas who had given birth within five years prior to the survey were included in the analysis. Descriptive analyses and binary logistic regression were used to analyse the data. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 21 publications
(27 reference statements)
31
46
1
Order By: Relevance
“…Facility not being open, transportation issues, absence of female provider and that health facility delivery was not necessary/not customary were more likely to be reported in the rural areas relative their urban counterparts. These findings are consistent with previous research studies [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…Facility not being open, transportation issues, absence of female provider and that health facility delivery was not necessary/not customary were more likely to be reported in the rural areas relative their urban counterparts. These findings are consistent with previous research studies [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, educated husbands influence the choice of place of delivery, which might be educated husbands would take the decision on place of birth for their wives. This finding supported by other studies conducted in Southeast Ethiopia and Ghana (20,26).…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that 73.44% (95% CI; 72.60, 74.26) of women deliver at home preceding the survey period. This finding was consistence with the study done Southeast Ethiopia (73.6%) (20), whereas it is higher than the study done at Afar, Ethiopia (65%), South Ethiopia (62.2%), Arba Minch town Ethiopia (33.2%), Akordet town, Eritrea (18%), urban community at Nigeria (35%), and Ghana (51.2%) (21)(22)(23)(24)(25)(26). The discrepancy might be the study area, setting deference, cultural attitude for health facility delivery, and infrastructure difference (access to the health facility, roads…).…”
Section: Discussionsupporting
confidence: 74%
“…In this analysis, mothers who were urban residents had higher odds of giving birth at a health facility compared with their rural counterparts. This finding is similar to the findings of studies conducted in Ethiopia and Ghana [69,72]. Urban women are more exposed to media messages related to the benefits of facility delivery.…”
Section: Health Facility Delivery Among Women Who Attended Four or Mosupporting
confidence: 90%